Isolation and characterization of a β(1-4) agarase of an epiphytic bacterial pathogen, Pseudoalteromonas gracilis B9, of the red alga, Gracilaria gracilis. - Schroeder, Declan Cosmo (Department of Molecular and Cell Biology, 2014)
Bibliography: p. 201-216.